The Role of Local Therapies in Maintaining ENT Health According to Ayurveda (International Journal of Ayurveda and Pharma Research, 2025)
To maintain the health of the individual along with the Tridoshas, Agni, Saptadhatu, Trimala has to be in synchronization with which the physiology of the individual runs normal. The Urdhwajatru Pradesh is the region in which Kapha Dosha is dominant. All the sensory organs lie in this region. Also, Shira Pradesh is most complex part in this region. The Shira i.e. brain controls all the body systems and all the centers for every activity lies in the brain. The supraclavicular region including the brain, sensory organs- viz., Netra, Karna, Nasa, Jivha, and Mukha, Danta, Gala, Manya, Skandha region comes under this Urdhwajatru terminology according to Ayurveda. The local therapies for Urdhwajatru Avayava can be used for preventive and therapeutic management according to the disease condition. It’s mode of action is depend on the nature of the drug used for the therapy and the structural tissue compliance. Also, it can be modified according to the the Ashthavidh Parikshya Bhava of the individual, Dashvidh Parikhsya Bhava for the specific disease in the individual as mentioned in Ayurveda. Aim- To study the importance of the local therapies in maintaining ENT health. Objectives- To study in detail the action of every local therapy which is beneficial for the management of ENT health. Material & Methods- Literature search from Ayurveda Samhitas to understand Rachana, Kriya and mode of action of local therapies in the Urdhwajatru Pradesh. Discussion- Benefits of the local therapies which can be done for prevention of ENT diseases and also can be modified conveniently to restore healthy life in daily routine. Conclusion- The ENT health can be enhanced by following local therapies, which will be helpful to balance Sthanik Dosha and improves Sthanik Bala